Avaliação do serviço de coleta para exame colpocitológico pela escala SERVQUAL - Nicole Jucá Monteiro; Luana Tainá Lima Amorim; Laura Maria Vidal Nogueira; Ivaneide Leal Ataíde Rodrigues; Suzana Rosa André
ABSTRACT Objective: To analyze women's perception of the quality of the service provided for colposcopy test in the city of Belém (PA), Brazil. Method: Quantitative-descriptive study on 400 women who underwent Pap test on the public healthcare network, using the Service Quality (SERVQUAL) model. We used the Cronbach's alpha index to measure the reliability of the scale, and data were analyzed by quartiles of the gaps of the dimensions: tangibility, responsiveness, reliability, assurance, and empathy. Results: The assurance dimension, corresponding to the knowledge and courtesy of staff, featured the highest degree of importance to users; and empathy, which corresponds to the staff's concern with women's needs, featured the lower degree. The most expressive negative gaps concerned the structure of services and the attitude of healthcare professionals when collecting the material. Conclusion: All gaps featured negative relationship between what was expected and perceived, expressing dissatisfaction regarding the service.